Digital marketing exploration, brand image on gen z buying interest in e-commerce - Putra, I Ketut Yasa; Darma, Gede Sri (International research journal of management, IT and social sciences, 2024)
This study aims to examine the influence of influencers, social media advertising, and service quality on purchase intention through brand image. In today’s digital era, influencers and social media advertising have a major impact on consumer behavior, while service quality plays an important role in shaping brand perception. This study is important to understand how the interaction between these factors affects purchase intention. The population of this study was Gen Z in Indonesia, with a sample of 208 people. Data were collected through an online questionnaire distributed via Google Form via social media. Respondents’ answers were measured using a 10-point scale. This study uses a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) to test the hypothesis. The results of the analysis show that influencers do not have a significant influence on purchase intention. In contrast, social media advertising, service quality, and brand image have a significant effect on purchase intention. In addition, influencers, social media advertising, and service quality also have a significant positive effect on brand image. These findings provide insight into how these factors influence and affect purchase intention, especially among Gen Z in Indonesia.